Rapid micropropagation and chemical profiling of in vitro plantlets and agarwood of Gyrinops walla Gaertn. by gas-chromatography and mass-spectrometry - S. Selvaskanthan; Lalith Jayasinghe; J. P. Eeswara (PLoS ONE, 2025)
Gyrinops walla Garten., which is an endemic and endangered species of Sri Lanka, produces the world’s most expensive agarwood used in perfume industry. The high demand for agarwood has resulted in indiscriminate felling of trees, thus threatening the survival of the species. The present study aimed to develop an efficient in vitro rapid multiplication technique to conserve the existing trees from extinction, by ensuring the sustainable supply of planting materials for commercial cultivations and to investigate the possibility of producing fragrance compounds by in vitro plantlets without felling trees. Efficient micropropagation protocol was developed from axillary buds and shoot tip explants. Murashige and Skoog (MS) medium supplemented with 1.0 mg/L BAP was the best for the establishment of both shoot tips (80.0%) and axillary buds (86.0%). Regenerated buds were further multiplied (10.6 ± 0.93 shoot buds/regenerated shoot) and elongated (4.0 ± 0.26 cm) by transferring to MS medium supplemented with 1.0 mg/L BAP, 0.1 mg/L IBA and 40 g/L sucrose. Highest in vitro rooting percentage (66.7%) was recorded in ½  MS medium supplemented with 1.0 mg/L IAA and 40 g/L sucrose. However, none of the shoots rooted on MS media could be acclimatized. Significantly higher percentage of rooted shoots (93.3%) were produced on sand medium without auxin treatment compared to shoots cultured on MS medium supplemented with 1.0 mg/L IAA (66%) and successfully acclimatized with 83.6% survival rate in a medium consisted of sand, topsoil, and compost (1:1:1 ratio). TLC fingerprints of ethyl acetate extracts of in vitro grown plantlets and agarwood produced similar spots at the retention factors (Rf) of 0.60, 0.66, and 0.87 under 15% methanol: 85% chloroform solvent system. Chemicals present in in vitro plantlets were identified and compared with the agarwood of naturally grown G. walla by GC-MS. Both natural agarwood and in vitro grown shoot extracts contained 4-Hydroxypyridine 1-oxide (23.2%), 2-tetradecene (16.3%), 1-hexadecene (0.3%), E-15-heptadecenal (19.8%), 18-norabietane (0.6%) and eicosane (0.4%). Present study successfully developed a protocol for rapid multiplication of G. walla and indicates the possibility of using of in vitro plantlets to produce agarwood resinous compounds.